Connecting pattern to process: Growth of spiral shell sculpture in the gastropod Nucella ostrina (Muricidae: Ocenebrinae). Issue 5 (3rd September 2018) - Webster, Nicole B.; Palmer, A. Richard
Abstract : Shell morphology is a well‐suited and underused system to examine the development of novel forms. The three‐dimensional structure produced (the shell) is separate from the largely two‐dimensional tissue that secretes it (the mantle), allowing us to disentangle the pattern from the process. Despite knowing a great deal about the mechanics of shell secretion (process), and the variety of shell shapes that exist (pattern), no effort has been made to understand how the mantle changes to produce different shell shapes. We investigated this question in the dimorphic snail Nucella ostrina, which exhibits both smooth and ribbed shells to determine how ribs are formed by the mantle. Rib thickenings are produced only in the outer calcitic shell layer and secreted by the distal Outer Mantle Epithelium (OME) with increased acid phosphatase activity. The evenly thick inner aragonitic layers are secreted by the proximal OME which expresses acid phosphatase. Here we show that locally thicker ribs in N. ostrina are produced by changing the dimensions of the distal OME: elongation in the direction of growth and increased cell height. This should increase the amount of shell material secreted, producing locally thicker shell (ribs). Preliminary evidence suggests this mechanism may be widespread in gastropods.